A model describing the development of road freight transport. - Kveiborg, Ole (Proceedings from the Annual Transport Conference at Aalborg University, 1998)
In an ongoing cooporation between Statistics Denmark and NERI we are developing a satellite model to a Danish macroeconomic model ADAM. That is a model linked to the macroecenomic development in ADAM, deriving the freight transport demand on Danish roads and energy consumption from this. A first operational version of the model is now ready. In the paper an overall view of the model is given, with simple calculation examples. A general discussion of the possible developments of the model into a dynamical model is given with focus on a specific area of the model.